Section 1: Health and Clinical Mangement: Health and Clinical Management – Comparing the Clinical Outcome of Computerized Strategies - Bergmann, J.; Managing Editor for the IMIA Yearbook Section on Health and Clinical Management (Yearbook of Medical Informatics, 2006)
To summarize current excellent research in the field of health and clinical management.Synopsis of the articles selected for the IMIA Yearbook 2006.Current research in the field of health and clinical management analyses impact and patient outcome of both established and recently presented approaches. Usability and effects of extracting data from computerized medical records for preventive care and surveillance issues are a topic as well as strategies for detecting adverse events.The best paper selection in the field of health and clinical management shows examples of excellent research on assessment, strategies and concepts for computerized health information management approaches. The articles emphasize the necessity of carefully considering health information systems regarding their outcome and compatibility with clinical routine. A concerted management of knowledge about evaluated health information management approaches will advance this trend and should lead to a more evidence-based design of the underlying systems.
Keywords: Medical Informatics; International Medical Informatics Association; Yearbook; Patient Care Management; Technology Assessment; Biomedical